The Conceptual Structure of EU Competition Law: Restrictive Agreements - Nagy, Csongor I (New Horizons in Competition Law and Economics series, 2024)
This is an Open Access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline, thanks to generous funding support from the Ministry of Culture and Innovation of Hungary and the National Research, Development and Innovation Fund. The Conceptual Structure of EU Competition Law provides a systematic overview of the key theoretical issues of restrictive agreements, by means of doctrinal analysis and comparative law. Engaging in both positivist and evaluative approaches, Csongor Istvan Nagy conceptualizes case-law in practical terms, outlining its paradigmatic changes and apparent contradictions.